The conflict of theory in Arabic grammar - Yaacob, Solehah@Nik Najah Fadilah (International Association of Computer Science and Information Technology Press (IACSIT), 2014)
The conflicts between schools of grammar among Arab traditional grammarians indicated that the differences on intellectual approaches occurred in modifying the Arabic Grammar system. For example that the Basra school used the philosophy and logic approaches in their analyzing, critique, modifying and replacing the system in Arabic Grammar. Otherwise, the Kufa school more concentrated on reading Holy Quran, Hadith and Arabic poetry such as Asim bin Abi Nujud, Hamzah Zayyat and Kisaai whose from Qura` Sab`ah among the thinkers of the school worked on informant sources meant they associated with something unexpected or different what normally happens. The views above had been discussed and clarified by some researchers, historians, linguists and grammarians that Basra school based on analogy and the Kufa school on anomaly approach. However, this research aims to verify the approach of Basra and Kufa schools in order to investigate their principles in implementing the linguistic argumentation.